(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2019)
The article deals with illicit traffic of cultural goods taking into consideration the actors involved in the entire commercial chain - from the so-called tombaroli to the most important museums and auction houses in the world. In particular, it focuses on the role of organized crime by reconstructing six case studies and underlining the economic and symbolic opportunity that the market of cultural goods offers to mafia organizations.